Evaluation of the Judicial Cases That Have Been Admitted to ondokuz Mayıs University Medical Faculty - Turla, Ahmet; Aydın, Berna (The Bulletin of Legal Medicine, 2007)
This study has been done with the aim of analysing the demographic characteristics, reasons for being admitted, and treatment results of the judicial cases between the ages of 0-18 who have been admitted to Ondokuz Mayıs University Medical Faculty Health Practice and Research Center and also with the aim of comparing this study with similar studies. The scope of this study includes 1118 judicial cases between the ages of 0-18 who have been admitted to Ondokuz Mayıs University Medical Faculty Health Practice and Research Center between 01.01.2004-31.12.2004. 36.6% of the 3057 judicial cases who have been admitted in 2004 are between the ages 0-18. 484 (43.3%) of these cases are female, 634 (56.7%) are male, and the average age is 8.54+-5.85 (0-18) years. Most of the cases were admitted to hospital in summer. It has been found that the most common reason (29.3%) for admission to hospital poisining and the second one (25.4%) was falling from high. The rate of children who were admitted for malicious injury was 17.4%, the rate of children were admitted for traffic accidents was 11.7%. Accidents in childhood are at the top of preventable health problems. Necessary precautions should be taken to make safe the environment and homes where children live and suitable safety tools should be used in order to do this. At the same time, these kind of cases should be informed by the people who intervene and it should be kept in mind that they are judicial cases which require public inquiry and proceeding.Key words: Judicial case, children, poisoning, accident
Keywords: judicial case; children; poisoning; accident